PENGEMBANGAN ALAT PERAGA PRAKTIKUM SEDERHANA DAN MODUL PENUNTUN PRAKTIKUM UNTUK MATERI LISTRIK DINAMIS PADA PELAJARAN FISIKA KELAS X SMA - Sari, Diana Novia; Lizelwati, Novia; Eliwatis, Eliwatis (Jurnal Pembelajaran MIPA, 2014)
The purpose of this study was to determine the practical props simple and practical guidance on material module dynamic power SMA valid and practical. Type of research is the development of the 4-D study design. research procedures can be divided into three stages, namely define, design and development. The research instrument used was a validation sheet, observation sheets, and sheets of questionnaire responses. Research instrument is developed by arranging the item instrument, test validation, test and analysis results practicality. The results showed that: 1). Simple props are valid with the percentage of 83% from the standpoint of physics education experts (validity), 2) guiding practicum module is valid with a percentage of 76% from the standpoint of physics education experts (validity) 2). The use of simple props and practical guidance module for dynamic electrical materials in lab activities did not experience significant barriers, according to its use in a practical sense observer and student assessment.Key words: development, simple props, practicality guidance module, dynamic power